The Influence of Internal Control and Implementation of Accounting Information Systems on The Quality of Regional Government Financial Reports: Study Of Bandung City Government Regional Work Units - Nasution, Sakti Muda; Karmana, Dedi; Kartikasari, Silvy; Fudsy, Mira Ismirani (LPPM STMIK Mardira Indonesia, 2023)
This study aims to ascertain how internal control and the use of accounting information systems affect the caliber of financial reports produced by local governments. The study's independent variables are internal control and the adoption of accounting information technology, whereas the dependent variable is the caliber of local government financial reports. Bandung City's regional government agencies (SKPD) work units make up the study's population. Employees from the Inspectorate, BPK, BPPD, Department of Communication and Information, Department of Library and Archives, Investment and Integrated Services Agency, Department of Spatial Planning and Infrastructure, and Administrative and Financial Assistant in the financial section, as well as those with decision-making authority like department heads and sub-section heads, were included in the purposive sample that was chosen using this sampling technique. Fifty respondents from these agencies were given questionnaires as part of the data collection process. Using SPSS 23.0 for Windows, multiple linear regression analysis is used in this study. The study's findings show that internal control makes up 47.2% of the total contribution to the quality of local government financial reports, which is positive and significant. Implementing accounting information systems makes up 23.6% of the total contribution and positively and significantly affects the quality of local government financial reports. Additionally, accounting information systems and internal control simultaneously impact 55.3% and 44.7%, respectively, on the caliber of local government financial reports.